2021
DOI: 10.1016/j.isci.2021.103062
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis by stroma confounds coculture studies

Abstract: Summary Signals provided by the microenvironment can modify and circumvent pathway activities that are therapeutically targeted by drugs. Bone marrow stromal cell coculture models are frequently used to study the influence of the bone marrow niche on ex vivo drug response. Here, we show that mesenchymal stromal cells from selected donors and NKTert, a stromal cell line, which is commonly used for coculture studies with primary leukemia cells, extensively phagocytose apoptotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, MSCs had been reported to contribute to phagocytosis in the embryo [ 24 ]. Follow-up studies in vitro confirmed phagocytosis and efferocytosis capacity of MSC [ 16 23 , 25 , 26 ]. Given the metabolic and mitochondrial impact of efferocytosis in macrophages [ 6 ], we reasoned that MSC efferocytosis may have a metabolic impact, and that it may inhibit their differentiation.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, MSCs had been reported to contribute to phagocytosis in the embryo [ 24 ]. Follow-up studies in vitro confirmed phagocytosis and efferocytosis capacity of MSC [ 16 23 , 25 , 26 ]. Given the metabolic and mitochondrial impact of efferocytosis in macrophages [ 6 ], we reasoned that MSC efferocytosis may have a metabolic impact, and that it may inhibit their differentiation.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have noted that MSCs can phagocytose bacteria [16,17], metallic particles from prosthetics [18,19,22], collagen [23], and apoptotic cells [20,21,[24][25][26]. However, dynamics and impact of this MSC activity remain poorly understood.…”
Section: Mesenchymal Stromal Cells Participate In Efferocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…Cells with a calcein intensity above a certain threshold and with PI intensities below a certain threshold were classified as alive. To avoid a possible influence of phagocytosis on relative percentages of alive cells (Herbst et al , 2021), absolute counts of alive CLL cells were used for all further analyses. These viabilities were normalised by division through viabilities in DMSO controls.…”
Section: Methodsmentioning
confidence: 99%